Kırgızistan Cumhuriyeti temel ekonomik göstergeler ve bankacılık sektörü - Asanov, Uran (My University, 2004)
Kyrgyz Republic is one of the first of Soviet Republics which obtained their independence from collapsed Soviet Union and chosed the free market economy as a main target in transformation process. It is sure that it required great efforts during desicion making of abondoning the old system and passing to the new one. It was a prerequisite of establishing a new legal base for free market economy since the old legal regulations were unsuitable for the new economy structure. As a result new law making was accelarated to catch the date. It is essential to note the legal regulations in the field of both banking and financial institutions. It is neadless to indicate that institutions like banks and other financial institutions form fundamental blocks of integral working free market economy. It is hard to believe in healthy economy transformation without arranging financial institutions. The legal regulationsThe law about the Central Bank of Kyrgyz Republic andThe law about Banks and Banking Activities which passed on June 1991 were the steps towards passing from single level financial structure to double level and modern banking system. The first chapter of my thesis dedicated to problems of transforming economy. The second and the third chapters mainly cover the banking sector of the country in the light of main economic indicators and in the conseptual framework of Kyrgyz economy. At the end some valuable proposals are put forward.

Kırgızistan eski Sovyetler Birliği ülkeleri içerisinde bağımsızlığını ilk kazanan cumhuriyetlerden biri olup, merkezî planlı ekonomiden serbest piyasa ekonomisine geçişi kendisine hedef seçmiş ve bu konuda çalışmalara başlamıştır.Elbette bir sistemi bir anda terk edip, yeni sistemi kurmaya kalkmak cesaretli bir adım olmakla beraber aynı zamanda zor bir karardır. Bunun komünist sisteminden kalma kanunlarla gerçekleştirilmesi imkansız olduğuna göre, serbest piyasa ekonomisinin yerleşmesi için yeni yasal düzenlemelerin yapılması hızlandırılmıştır. Bu yasal düzenlemelerin içinde bankacılık ve mali kurumlar alanındaki düzenlemelerin önemi kelimelerle ifade edilmeyecek kadar büyüktür, zira entegre olunmaya çalışan piyasa ekonomisinin temel unsurları bankalar ve mali kurumlardır. Mali kurumları oluşturmadan piyasa ekonomisine sağlıklı bir geçiş yapmak mümkün değildir. Haziran 1991'de kabul edilmiş Kırgız Cumhuriyeti Merkez Bankası Hakkında Kanun ve Bankalar ve Bankacılık Faaliyetleri Hakkındaki kanunlarla Kırgızistan'da tek düzeyli mali yapıdan iki düzeyli mali yapıya geçişi ve modern bankacılık sisteminin yasal temellerinin atılması doğrultusunda atmış olduğu ilk adım oldu. Çalışmanın birinci bölümünde geçiş ekonomileri özetlenerek tezin ikinci ve üçüncü bölümlerinde ağırlıklı olarak bankacılık sektörü olmak üzere temel ekonomik göstergelere de göz atmak suretiyle Kırgızistan ekonomisi bağlamında incelemekte ve bazı öneriler sıralanmaktadır.
Keywords: Banka ve bankacılık; Ekonomi; Ekonomik Gelişi_Kırgızistan; Finansman ekonomisi